Effects of acute organophosphate poisoning on pituitary target gland hormones at admission, discharge and three months after poisoning: A hospital based pilot study - Pinaki Dutta (Indian Journal of Endocrinology and Metabolism, 2015)
Background: Organophosphate compound (OPC) poisoning is common in the developing countries such as India. The acute and later effects of OPC poisoning on pituitary and target gland hormones is largely unknown. Materials and Methods: This prospective study was conducted at Postgraduate Institute of Medical Education and Research between January 2012 and March 2013. Fourteen patients (8 males, age 18-50 years) with acute OPC poisoning were included in the study based on the history and clinical features, documented decreased in plasma cholinesterase activity or presence of the OPC in gastric lavage/blood samples. The hormonal parameters were done at baseline, at the time of discharge and at three months of follow-up. Results: A total of 14 patients out of 46 with the mean age of 30.1 ± 10.3 years were finally eligible for the study. Hormonal alterations at admission were similar to sick euhormonal syndrome. Overall 7 of them had nine hormonal deficits at three months of follow up, 4 having sub normal basal cortisol level and two each had low testosterone and growth hormone and only one had thyroxine deficiency. Conclusion: Acute organophosphate poisoning results in endocrine dysfunction akin to sick euhormonal syndrome. However, in a small subset of patients, varying level of hormonal insufficiency may occur either at admission or later. These observations need re-validation in a larger group of patients with specific OPC.